Crystal chemistry and compressibility of Fe0.5Mg0.5Al0.5Si0.5O3 and FeMg0.5Si0.5O3 silicate perovskites at pressures up to 95 GPa - Koemets, Iuliia; Wang, Biao; Koemets, Egor; Ishii, Takayuki; Liu, Zhaodong; McCammon, Catherine; Chanyshev, Artem; Katsura, Tomo; Hanfland, Michael; Chumakov, Alexander; Dubrovinsky, Leonid (Frontiers in Chemistry, 2023)
Silicate perovskite with the mineral name bridgmanite is the most abundant mineral in the Earth's lower mantle. We investigated crystal structures and equations of state of two perovskite-type Fe 3+ -rich phases, FeMg0.5Si0.5O3 and Fe0.5Mg0.5Al0.5Si0.5O3, at high pressures employing singlecrystal X-ray diffraction and Synchrotron Mössbauer spectroscopy. We solved their crystal structures at high pressures and found that FeMg0.5Si0.5O3 phase adopts a novel monoclinic double-perovskite structure with the space group of P21/n at pressures above 12 GPa whereas Fe0.5Mg0.5Al0.5Si0.5O3 phase adopts an orthorhombic perovskite structure with the space group of Pnma at pressures above 8 GPa. Pressure induces an iron spin transition for Fe 3+ in a (Fe0.7,Mg0.3)O6 octahedral site of FeMg0.5Si0.5O3 phase at pressures higher than 40 GPa. No iron spin transition was observed for Fe0.5Mg0.5Al0.5Si0.5O3 phase as all Fe 3+ are located in a bicapped prism sites, which has a larger volume than an octahedral site of (Al0.5,Si0.5)O6.